1997
DOI: 10.1007/s005200050098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cost of home care for terminally ill cancer patients

Abstract: The aim of this work was to carry out a cost evaluation of the home care programme for terminally ill cancer patients run by the Istituto Oncologico Romagnolo (I.O.R.) in the areas of Forlì, Cesena, Ravenna and Rimini (Romagna, Italy). To determine effective home care direct costs, we first selected 1 week of care as an observation unit. We then proceeded to assess the medical and nursing care units together with the clinical protocols administered for each patient. The Karnofsky Performance Status (KPS) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
3
13
1
1
Order By: Relevance
“…This is consistent with the findings of an Italian study that reported a negative correlation between a patient's Karnofsky Performance Status score (modified PPS) and average weekly home-based care costs. 24 However, these results are not directly comparable to ours, as the Italian study did not assess utilization by separate service categories.…”
Section: Discussionmentioning
confidence: 61%
“…This is consistent with the findings of an Italian study that reported a negative correlation between a patient's Karnofsky Performance Status score (modified PPS) and average weekly home-based care costs. 24 However, these results are not directly comparable to ours, as the Italian study did not assess utilization by separate service categories.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the economic results were not analysed in as much detail as would be necessary for a reliable comparison. A more recent Italian study by Maltoni et al proved the cost-effectiveness of a specially developed home care programme for terminally ill cancer patients [10]. The group of patients followed in the study was also quite heterogeneous.…”
Section: Comparisonmentioning
confidence: 98%
“…Quantitative comparison is not easy, however, because Maltoni et al (intentionally) omitted costs of the very last week (spent by many patients in hospital) -and because the Italian cost data refer to a special home care programme involving specialists in palliative care, etc. The average weekly cost was reported to rise from 180 ECU 15 weeks before death, to 221 ECU 1 week before death (c22.8%) [10].…”
Section: Comparisonmentioning
confidence: 99%
“…), or overall home‐based service utilisation without examining each service category individually (Maltoni et al . , Grande et al . , Tang , Gagnon et al .…”
Section: Introductionmentioning
confidence: 99%